2021
DOI: 10.1002/iid3.419
|View full text |Cite
|
Sign up to set email alerts
|

A territory‐wide study on the factors associated with recurrent asthma exacerbations requiring hospitalization in Hong Kong

Abstract: Background: The real-world relationships between the demographic and clinical characteristics of asthma patients, their prehospitalization management and the frequency of hospitalization due to asthma exacerbation is poorly established. Objective: To determine the risk factors of recurrent asthma exacerbations requiring hospitalizations and evaluate the standard of baseline asthma care. Methods: A territory-wide, multicentre retrospective study in Hong Kong was performed. Medical records of patients aged ≥18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Some concrete examples include recurrence of hospitalization for cardiovascular events [1,2], recurrent diseases and infections like COVID-19 [3], pneumonia [4,5], pneumococcus [6], staphylococcus aureus (cf. section Example 1: Staphylococcus aureus infection data) [7,8], asthma [9,10] and malaria (cf. section Example 2: Childhood malaria data) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some concrete examples include recurrence of hospitalization for cardiovascular events [1,2], recurrent diseases and infections like COVID-19 [3], pneumonia [4,5], pneumococcus [6], staphylococcus aureus (cf. section Example 1: Staphylococcus aureus infection data) [7,8], asthma [9,10] and malaria (cf. section Example 2: Childhood malaria data) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Some concrete examples include recurrence of hospitalization for cardiovascular events (Gibson et al, 2017; Varma et al, 2021), recurrent diseases and infections like COVID-19 (Dos Santos et al, 2021), pneumonia (Ramjith et al, 2021; Barakat et al, 2021), pneumococcus (Hernstadt et al, 2020), staphylococcus aureus (cf. Section 5.1) (Akinboyo et al, 2018; Abdulgader et al, 2019), asthma (Chan et al, 2021; Feng et al, 2021) and malaria (cf. Section 5.2) (Lawpoolsri et al, 2019; Ghosh et al, 2020; Kakuru et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2,69,73 For example, a recent study from India estimated that only 6.8%-10.3% of patients with asthma who were indicated for ICS-based regimens were actually prescribed them, 74 while a study from Hong Kong showed that only 64.5% of patients hospitalized for asthma exacerbations had received ICS prior to hospitalization, and a lack of ICS use was determined as a significant predictor of increased asthma-related hospital admissions. 75 In Singapore, a similar trend was observed that suggested association between poor guideline adherence and increased frequency of asthma-related ED readmissions. 73 The extent of guideline adherence appears to be related to the proper care coordination and specialist referrals noted above, as studies have suggested that PCPs/GPs are more likely to prescribe SCS and less likely to prescribe ICS than respiratory specialists.…”
Section: Economicsmentioning
confidence: 55%
“…• HCPs may not be familiar with the recently detailed risks of SCS in patients with asthma, [23][24][25][26][27][28][29][30][31] or recent asthma treatment guideline updates discouraging the use of SCS. [73][74][75] • Physicians may overestimate patient asthma control, 76 which could lead to prescribing inadequate treatments and, thus, more rapid disease progression and/or exacerbations that require SCS.…”
Section: Physical Environmentmentioning
confidence: 99%
See 1 more Smart Citation